ANALISIS PENGARUH ULASAN PELANGGAN, CITRA MERK, DAN INTENSITAS PROMOSI TERHADAP PEMBUATAN KEPUTUSAN PEMBELIAN (Studi Empiris Pada Pelanggan E-Commerce Shopee di Padang Panjang) - Auna Dwi Fadhlillah; Retno Hidayati (Diponegoro Journal of Management, 2022)
This study aims to analyze the effect of customer reviews, brand image, and promotion intensity on purchasing decision making (empirical study on Shopee ecommerce customers in Padang Panjang), as well as to determine the most influential variables on purchasing decision making, so that it can be used as a review in develop strategies to improve customer purchasing decisions. The population in this study are Shopee e-commerce customers in Padang Panjang City who are over 17 years old and have made a purchase at Shopee at least once in the past year. The number of samples used is 150 respondents selected by purposive sampling, and using non-probability sampling technique using multiple linear regression analysis. The results of this study indicate that customer reviews have a positive and significant effect on making purchasing decisions. Brand image has a positive and significant effect on making purchasing decisions. Promotion intensity has a positive and significant effect on purchasing decision making. Keywords: Customer reviews, Brand image, Promotion intensity, Purchase decision making.